2011
DOI: 10.1107/s1600536811020642
|View full text |Cite
|
Sign up to set email alerts
|

Cyclobenzaprinium salicylate

Abstract: In the title molecular salt [systematic name: 3-(5H-dibenzo[a,d]cyclohepten-5-ylidene)-N,N-dimethyl-1-propanaminium 2-hydroxybenzoate], C20H22N+·C7H5O3−, the benzene rings of the cyclobenzaprinium cation are inclined with a dihedral angle of 61.66 (7)°. An intramolecular O—H...O hydrogen bond occurs within the salicylate anion, generating an S(6) ring. In the crystal, the cation and anion are linked by an N—H...O interaction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…The benzene rings of the cation (C1-C6) and anion (C17-C22) are inclined at an angle of 15.00 (9) Å while the benzene rings of the neutral molecules (C9-C14) and (C24-C29) are inclined at an angle of 11.08 (9) Å . The bond lengths of the ions and molecules are comparable with those in previously reported structures (Fun et al, 2011;Mani et al, 2015;Mathlouthi et al, 2014).…”
Section: Structure Descriptionsupporting
confidence: 87%
“…The benzene rings of the cation (C1-C6) and anion (C17-C22) are inclined at an angle of 15.00 (9) Å while the benzene rings of the neutral molecules (C9-C14) and (C24-C29) are inclined at an angle of 11.08 (9) Å . The bond lengths of the ions and molecules are comparable with those in previously reported structures (Fun et al, 2011;Mani et al, 2015;Mathlouthi et al, 2014).…”
Section: Structure Descriptionsupporting
confidence: 87%
“…For structurally related tricyclic antidepressants, see: Cimolai (2009); Commissiong et al (1981); Katz & Dube (1988). For related structures, see: Bindya et al (2007); Fun et al (2011); Portalone et al (2007). For standard bond lengths, see Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%
“…Cyclobenzaprine has been considered structurally related to the first-generation tricyclic antidepressants (Commissiong et al, 1981;Katz & Dube, 1988;Cimolai, 2009). The crystal structures of amitriptylinium picrate (Bindya et al, 2007), 5-[3-(dimethylamino)propyl]-10,11-dihydro-5H-dibenz [a,d][7]annulen-5-ol (Portalone et al, 2007) and cyclobenzaprinium salicylate (Fun et al, 2011) have been reported. In view of the importance of yclobenzaprine, this paper reports the crystal structure of the title compound, C 20 H 22 N + .…”
Section: Data Collectionmentioning
confidence: 99%
“…For its structural relationships to first-generation tricyclic antidepressants, see: Commissiong et al (1981); Katz & Dube (1988); Cimolai (2009). For related structures, see: Bindya et al (2007); Jasinski, Pek et al (2010); Jasinski, Butcher et al (2010); Fun et al (2011); Siddegowda et al (2011). For standard bond lengths, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%